The relationship between contingency leadership characteristics and employee's job satisfaction / Nurul Fatin Nabila Norrudin - Norrudin, Nurul Fatin Nabila
This study was conducted to identify the relationship between Contingency Leadership Style and employee's job satisfaction at Brooke Dockyard & Engineering Works Corporation. For data obtained through correlation method, this research was analyzed by using Pearson Correlation test through Statistical Package for Social Science (SPSS) version 20.0. On the other hand, this study was obtained through questionnaires and the consistency of most findings with results showed that Contingency Leadership did not influence much in employee's job satisfaction.